Development of ZnO components for Flash sintering at low temperatures - Ferreira, Nuno Gonçalo (2018)
Flash sintering is a non-conventional sintering method proposed in 2010. Flash combines the use of electric field and temperature to promote densification of materials in seconds (<60 s) at lowered temperatures. The Flash temperature (Tf) is defined as the temperature at which the power supply switches from voltage to current control mode and sintering starts. The combination of the electric field and furnace atmosphere during Flash experiments gives a possibility to significantly decrease Tf of ZnO among other materials. Conventional sintering temperature of pure ZnO is close to 1200 ºC, while the use of a water assisted Flash sintered apparatus allows the densification of ZnO to occur at room temperature. However, a comprehensive study of the water role and the effect of other atmospheres on the Flash sintering of ZnO is yet missing. In the present work, the influence of such atmospheres as air, argon (Ar), and nitrogen/hydrogen mixture (N2/H2) on Flash sintering of pure ZnO is studied with and without water.. So far, it is possible to Flash sinter ZnO between 25 and 30 ºC using wet Ar and N2/H2, respectively. However, without the water vapour, the Flash temperature increases to 100 ºC in Ar and 144 ºC in N2/H2, highlighting the important role of the water in the ZnO conductivity and defect chemistry, which directly influences the value of Tf and the microstructural evolution in the Flash sintering. The influence of doping ZnO with Al both on the onset temperature of Flash sintering and on the microstructure of the sintered pellets is also studied under the conditions previously used for undoped ZnO. In addition, an energetic sustainability study of Flash sintered commercial alumina, Rapox Brown from Rauschert, is presented as a result of a partnership between the University of Aveiro and Rauschert Portuguesa.